Sasak Traditional Marriage System in Avoiding Conflict and Preventing Disharmony Between Families in the Modern Era - M. Qamaruzzam Alawiyyin Batin Zohiro; Paenal Juni Harian; Khairul Nur Hazami; Santiani Santiani; Ananda Wahidah (JED (Jurnal Etika Demokrasi), 2024)
Family encouragement and custom often force someone to get married even though the person is not fully ready, often creating conflict within the family. This research reveals that the Sasak traditional marriage system on Lombok Island legalizes kidnapping marriages so that the potential for conflict is increasingly wide open. This study aims to examine and analyze the role of the Sasak marriage customary system in an effort to reduce the potential for conflict due to merarik kodek which can result in disharmony between the couple's families. This research uses a qualitative method with an ethnographic approach carried out through observation and in-depth interviews conducted with 19 informants. The results show that conflicts that can occur due to child marriage can be mitigated by the merarik customary system, even though the custom itself triggers potential conflicts that can result in disharmony between the couple's families. The first three processes of merarik, namely maling, besejati and selabar, will create the potential for conflict, and the next three processes, ngawinan, nyongkolan and bales lampak nae, will reduce the potential for conflict. So, it is concluded that the Sasak marriage system can reduce conflict due to the tradition of merarik kodek.